Hydrolysis of cellulose using cellulase physically immobilized on highly stable zirconium based metal-organic frameworks. (December 2018) - Ahmed, Ibrahim Nasser; Yang, Xiu-Li; Dubale, Amare Aregahegn; Li, Ruo-Fei; Ma, Yi-Ming; Wang, Lu-Ming; Hou, Gui-Hua; Guan, Rong-Feng; Xie, Ming-Hua
Graphical abstract: Highlights: Physical immobilization of cellulase onto MOF was achieved for the first time. >85% of maximum activity of immobilized cellulase can be maintained at 80 °C. >90% of maximum activity can be maintained between pHs 3–6 of hydrolysis. >72% of residual activity was maintained after 10 cycles. >65% of maximum activity could be reserved after 30 days of storage. Abstract: Developing a new cellulase-MOF composite system with enhanced stability and reusability for cellulose hydrolysis was aimed. Physical adsorption strategy was employed to fabricate two cellulase composites, and the activity of composite was characterized by hydrolysis of carboxymethyl cellulose. The NH2 functionalized UiO-66-NH2 MOF exhibited higher protein loading than the precursor UiO-66, due to the extra anchor sites of NH2 groups. The immobilized cellulase showed enhanced thermostability, pH tolerance and lifetime. The maximum activity attained at 55 °C could be kept 85% when used at 80 °C, and the residual activities were 72% after ten cycles and 65% after 30 days storage. The abundant NH2 and COOH groups of MOF adsorb cellulase and enhance its stability, and the resulted heterogeneity offered the opportunity of recovering composite via mild centrifuge. The findings suggest the promising future of developing cellulase-MOF composite with ultrahigh activities and stabilities for practical application.